2016
DOI: 10.1136/heartjnl-2015-309110
|View full text |Cite
|
Sign up to set email alerts
|

‘End-stage’ heart failure therapy: potential lessons from congenital heart disease: from pulmonary artery banding and interatrial communication to parallel circulation

Abstract: The final therapy of ‘end-stage heart failure’ is orthotopic heart, lung or heart-lung transplantation. However, these options are not available for many patients worldwide. Therefore, novel therapeutical strategies are needed. Based on pathophysiological insights regarding (1) the long-term impact of an obstructive pulmonary outflow tract in neonates with congenitally corrected transposition of the great arteries, (2) the importance of a restrictive versus a non-restrictive atrial septum in neonates born with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 33 publications
0
17
0
3
Order By: Relevance
“…Recent studies reported therapies for end-stage DCM including cardiac resynchronization therapy, restrictive atrial septal defect (ASD) creation, and pulmonary artery banding [4]. Transcatheter ASD creation reduced left atrial pressure and brain natriuretic peptide levels [5].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported therapies for end-stage DCM including cardiac resynchronization therapy, restrictive atrial septal defect (ASD) creation, and pulmonary artery banding [4]. Transcatheter ASD creation reduced left atrial pressure and brain natriuretic peptide levels [5].…”
Section: Discussionmentioning
confidence: 99%
“…On considering pathophysiological-based therapeutic strategies by combining catheter and/or surgical procedures with disease-targeted drug therapies, we might be able to avoid extracorporal life-support with a higher risk/benefit ratio. 7 The fact that an infant with a cytomegalovirus myocarditisassociated heart failure and persistent pulmonary hypertension was kept alive with re-ducting was surprising, though not by the natural setting of a non-restrictive atrial septal defect together with a restrictive ventricular septal defect. We could not determine if the persistence of congenital shunts ameliorated or worsened the viral myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…Preserved Right Ventricular Function -PRV) u dobnoj skupini prije druge godine života. 68,72 Tran splantaciju srca započeli smo 2011. god. s krivuljom preživljenja od 75%.…”
Section: Raspravaunclassified